Morphological Characterization of Doe Kacang Goat in the Dry Land Area - Veronika Yuneriati Beyleto; N Hilmia (Indonesian Center for Animal Research and Development (ICARD), 2023)
This study was conducted to select a breed based on the morphological characteristics of Kacang goats in the dry land area, by assessing 31 doe Kacang goats. Semi-intensive raising system is carried out (without giving concentrate), yet water; forage (such as Gliricidia sepium leaves, Sesbania grandiflora leaves, Leucaena leucocephala leaves) and local grass are given by applying ad libitum method. Description of morphological characteristics, Pearson's correlation between body weight and body size, and body index, were analyzed using SPSS 25.0 program. The result of descriptive analysis for BW, BL, WH, CG, CW, CD, RW, RH, RL, HL, HW, and HH are 20.72±3.26 kg, 44.34±8.17 cm, 55.42±7.84 cm, 62.68±7.12 cm, 10.98±2.07 cm, 22.74±2.12 cm, 8.44±1.38 cm, 54.96±6.44 cm, 12.55±0.85 cm, 14.07±0.55 cm, 10.19±0.36 cm, dan 11.69±0.45 cm respectively. The value of the morphological index for WS, BI, DI, LI, PI, B, HS, FL, and CI are 0.78+0.12, 71.06±12.38, 0.42±0.06, 0.81±0.18, 67.55±11.93, 0.43±0.08, 11.18±5.78, 32.68±7.40, dan 72.48±2.82, respectively. The conclusion is that the body weight and body measurements in the dry land area are still below the quality National standards of Indonesia. The correlation coefficient of body weight with body size is in the positive range of moderate to high except, the correlation of body weight with head height which shows a negative correlation. The correlation coefficient of body weight with the morphological index is in the low positive range except for the correlation coefficient of body weight with width slope, balance, and height slope which has a negative correlation coefficient.